Examining Racial Disparities in Colon Cancer Clinical Delay in the Colon Cancer Patterns of Care in Chicago Study - Jones, Lindsey A. (Ann Epidemiol, 2017)
PURPOSE: We explored a potential racial disparity in clinical delay among non-Hispanic (nH) Black and White colon cancer patients and examined factors that might account for the observed disparity. METHODS: Patients aged 30–79 with a newly diagnosed colon cancer from 2010–2014 (N=386) were recruited from a diverse sample of nine public, private and academic hospitals in and around Chicago. Prolonged clinical delay was defined as ≥60 or ≥90 days between medical presentation (symptoms or a screen-detected lesion) and treatment initiation (surgery or chemotherapy). Multivariable logistic regression with model-based standardization was used to estimate the disparity as a difference in prevalence of prolonged delay by race. RESULTS: Prevalence of delay in excess of 60 days was 12 percentage points (95% CI: 2%, 22%) higher among nH Blacks versus Whites after adjusting for age, facility and county of residence. Travel burden (time and distance traveled from residence to facility) explained roughly one-third of the disparity (33%, p=0.05),individual and area-level socioeconomic status measures explained roughly one-half (51%, p=0.21), and socioeconomic measures together with travel burden explained roughly four-fifths (79%, p= 0.08) CONCLUSIONS: Low socioeconomic status and increased travel burden are barriers to care disproportionately experienced by nH Black colon cancer patients.